War and state formation in Syria - Cicek, M. Talha., author.
1 online resource (xiii, 293 pages)
Keywords: "During the First World War, Cemal Pasha attempted to establish direct control over Syrian and thereby reaffirm Ottoman authority there through various policies of control, including the abolishment of local intermediaries. Elaborating on these Ottoman policies of control, this book assesses Cemal Pasha's policies towards different political groups in Syrian society, including; Arabists, Zionists, Christian clergymen and Armenian immigrants. The author then goes on to analyse Pasha's educational activities, the conscription of Syrians- both Muslim and Christian, and the reconstruction of the major Syrian cities, assessing how these policies contributed to his attempt to create ideal Ottoman citizens. An important addition to existing literature on the social and political history of World War I, and contributing a new understanding of Ottoman Syria, and its transformation into a nation-state, this book will be of interest to students and scholars with an interest in state formation, Politics and History"--